Treatment cascade for patients with multidrug- or rifampicin-resistant tuberculosis and associated factors with patient attrition in southeastern China: a retrospective cohort study - Bin Chen; Xinyi Chen; Yanli Ren; Ying Peng; Fei Wang; Lin Zhou; Biao Xu (Elsevier, 2023)
Objectives: To address gaps in health services for multidrug- or rifampicin-resistant tuberculosis (MDR/RR-TB), a treatment cascade model was used to evaluate patient retention and attrition at each successive step required to achieve a successful treatment outcome. Methods: From 2015-2018, a four-step treatment cascade model was established in patients with confirmed MDR/RR-TB in southeast China. Step 1: diagnosis of MDR/RR-TB, step 2: Initiation of treatment, step 3: still under treatment at 6 month and step 4: cure or completion of MDR/RR-TB treatment, with each successive step including a gap that shows attrition of patients between steps. The retention and attrition of each step were graphed. Multi-variate logistic regression was carried out to further identify potential factors associated with the attrition. Results: In the treatment cascade consisting of 1752 MDR/RR-TB patients, the overall patient attrition rate was 55.8% (978/1752), with 28.0% (491/1752), 19.9% (251/1261), and 23.4% (236/1010) of patients attrition in the first, second, and third gap. Factors associated with MDR/RR-TB patients not initiating treatment included age ≥60 years (OR:2.875), and time for diagnosis ≥30 days (OR: 2.653). Patients who were diagnosed with MDR/RR-TB through rapid molecular test (OR: 0.517) and non-migrant residents of Zhejiang Province (OR: 0.273) both exhibited a lower likelihood of attrition during the treatment initiation phase. Meanwhile, old age (OR: 2.190) and non-resident migrants to the province were factors associated with not completing ≥ 6 months of treatment. Old age (OR: 3.883), retreatment (OR: 1.440), and time to diagnosis ≥30 days (OR: 1.626) were factors contributing to poor treatment outcomes. Conclusion: Several programmatic gaps were identified in the MDR/RR-TB treatment cascade. Future policies should provide more comprehensive support for vulnerable populations to improve the care quality at each step.